Televisi dalam Ruang Keluarga: Menyoal Menonton Televisi sebagai Praktik Konsumsi dalam Konfigurasi Ruang Domestik - Triwardani, Reny (Jurnal Ilmu Komunikasi, 2011)
Abstract: For modern society, television has played an important role in almost all aspects of life. Television was born due to the development of mass communications technology that gives the influences of human civilization. The presence of television in the living room has its own implications. Television that placed and was watched in the domestic sphere, in the house, is more than looking the television screen. Configuration viewing space has consequences for the viewing patterns of everyday family life. This paper examines spatial configuration and dynamics of the television media use in everyday family life. The television in a particular spatial configuration, in the house, determine differences viewing patterns.Abstrak: Bagi masyarakat modern, televisi telah memainkan peranan penting di hampir semua aspek kehidupan. Televisi lahir karena perkembangan teknologi komunikasi massa yang memberikan pengaruh dalam peradaban manusia. Keberadaan pesawat televisi dalam ruang keluarga memiliki implikasi tersendiri. Televisi yang ditempatkan dan ditonton dalam ruang domestik, di dalam rumah, bukanlah aktivitas menatapkan mata ke layar televisi semata-mata. Konfigurasi ruang menonton memiliki konsekuensi terhadap pola menonton yang berlangsung dalam kehidupan keluarga sehari-hari. Tulisan ini mengkaji konfigurasi ruang menonton televisi dan dinamika penggunaan media televisi dalam kehidupan keluarga sehari-hari. Dalam kaitan ini, televisi yang berada dalam konfigurasi ruang tertentu, di dalam rumah, menentukan keberbedaan pola menonton.Â Â